Students’ Motivation in Learning Mathematics Using Uno Math Media - Ahmad Lutfi; Husnul Khatimah Rusyid; Ahmad Mukhibin; Mochamad Abdul Basir (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
Learning motivation is one of the important aspects in learning mathematics. Students with high motivation will enable enthusiasm and tend to obtain high mathematics learning achievement. Students often feel bored in learning mathematics because mathematics learning is abstract and difficult. Learning by utilizing games in several studies has proven to have a positive effect on learning mathematics. This study aims to describe students' motivation to learn mathematics after using Uno Math media. This study used a quantitative approach with descriptive method. The population in this research were all grade X students in one of the high senior schools in Semarang. Sampling was conducted using random sampling technique in which class X MIPA 1 was selected as the research sample with a total of 25 students, consisting of 5 male students and 20 female students. The results showed that students' motivation to learn mathematics reached 69.96% in the high category. Teachers can make use of Uno Math media in learning mathematics to help students understand formulas, and make students not bored in learning mathematics because there is a new method in teaching mathematics with fun